Topological defects and anisotropic development during pre-graphitization - Francas, Gabriel; Martin, Jacob; Suarez-Martinez, Irene; Marks, Nigel (2023)
Aligned graphenic fragments of varying size, mimicking those found in carbons carbonized through a mesophase, are found to self-assemble towards structures of varying anisotropy when annealed using molecular dynamics simulations. These models enable us to probe the range of topological features present in carbons of varying anisotropy where we find significant differences in the defects present. We conclude that the screw dislocation is the dominant annealable defect in graphitizable carbons, while a persistence of saddle-shaped defects may make some carbons less graphitizable. These findings contribute to the ongoing questions surrounding the factors which determine precursor graphitizability.